Photoresponse on nanostructure of ZnO thin films prepared by sol-gel spin coating technique: article - Md Shokor, Amir Akmal; Abd Rasheid, Norulhuda (2013)
Zinc oxide (ZnO) thin films have been prepared by sol-gel spin coating method on glass substrate. ZnO thin films at different thickness were investigated. Optical properties measure from UV-Vis spectrophotometer shows the optical band gap increased when the thin film thickness increased. The surface roughness also increased as the thickness increased shows from atomic force microscopy (AFM) measurement Field emission scanning electron microspcopy (FESEM) images reveal the increasing of porous among grains when the ZnO thin film increased. Current-Voltage (I-V) measurement result shows there is photo response characteristic on ZnO thin film when illumination state show higher conductivity than dark state.